An approach of differential capacitor sensor for landslide monitoring - Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn (International Journal of GEOMATE, 2015)
A lot of lives and properties are lost in every year all over the world, due to various geological catastrophes, landslide or land - slip is among one of them. Nowadays, both manual and electronic monitoring systems ar e used to predic t the landslide . The manual monitoring system is laborious, has many limitations and most of the cases it is not practicable. Conversely, most of the electronic systems are complex and expensive. Most of the natural calamities occur without prior notice as a result, it damages the monitoring instrument as well. The monitoring sensor system should be planned as a spread network with a simple positional identification device such as RFID; hence the system can send the real time data without interrupt. In addi tion, the network should have a self - recovery, self - directed operation and actual data transmission facility in a critical situation. A distributed node network needs a lot of sensors with complex structure and it is expensive too. This paper describes a s imple and low cost system which comprises an underground pretension cable with a capacitor gauge sensor attached at one end. A wireless sensor network has been proposed for a simple landslide monitoring system using RFID. The sensing node network can opera te by initializing mode, measuring mode and urgent mode. The system is able to select automatically any one of the operating mode depending on the situation , which makes it a robust and dynamic control of real time data transmission system. A mathematical model has been developed for the system and verified by simulation. The result shows that an early prediction of the landslide is possible by using the proposed system.